A study on the advertising campaign, insight and justifying my job profile in context of Ogilvy & Mather, Bangladesh - Zulfiqur, Kazi Taslim (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2013.